Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

What are the zeros of the quadratic function [tex]$f(x)=6x^2 + 12x - 7$[/tex]?

A. [tex]$x=-1-\sqrt{\frac{13}{6}}$[/tex] and [tex][tex]$x=-1+\sqrt{\frac{13}{6}}$[/tex][/tex]

B. [tex]$x=-1-\frac{2}{\sqrt{3}}$[/tex] and [tex]$x=-1+\frac{2}{\sqrt{3}}$[/tex]

C. [tex][tex]$x=-1-\sqrt{\frac{7}{6}}$[/tex][/tex] and [tex]$x=-1+\sqrt{\frac{7}{6}}$[/tex]

D. [tex]$x=-1-\frac{1}{\sqrt{6}}$[/tex] and [tex][tex]$x=-1+\frac{1}{\sqrt{6}}$[/tex][/tex]


Sagot :

To determine the zeros of the quadratic function [tex]\( f(x) = 6x^2 + 12x - 7 \)[/tex], we need to solve the equation [tex]\( 6x^2 + 12x - 7 = 0 \)[/tex]. The general form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex], where [tex]\( a = 6 \)[/tex], [tex]\( b = 12 \)[/tex], and [tex]\( c = -7 \)[/tex] in this case.

The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

Step-by-step:

1. Identify the coefficients:
[tex]\[ a = 6, \quad b = 12, \quad c = -7 \][/tex]

2. Calculate the discriminant ([tex]\( \Delta \)[/tex]):
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Plugging in the values:
[tex]\[ \Delta = 12^2 - 4 \cdot 6 \cdot (-7) \][/tex]
[tex]\[ \Delta = 144 + 168 \][/tex]
[tex]\[ \Delta = 312 \][/tex]

3. Apply the quadratic formula:
[tex]\[ x = \frac{-12 \pm \sqrt{312}}{12} \][/tex]

4. Simplify the expression inside the square root:
[tex]\[ \sqrt{312} = 2 \times \sqrt{78} = 2 \times \sqrt{6 \times 13} = 2 \sqrt{78} \][/tex]

5. Substitute [tex]\(\sqrt{312}\)[/tex] back into the quadratic formula:
[tex]\[ x = \frac{-12 \pm 2\sqrt{78}}{12} \][/tex]

6. Simplify the fraction:
[tex]\[ x = \frac{-12}{12} \pm \frac{2\sqrt{78}}{12} \][/tex]
[tex]\[ x = -1 \pm \frac{\sqrt{78}}{6} \][/tex]

Since [tex]\(\sqrt{78}\)[/tex] simplifies to [tex]\( \sqrt{6 \times 13}\)[/tex]:

[tex]\[ x = -1 \pm \sqrt{\frac{78}{36}} = -1 \pm \sqrt{\frac{13}{6}} \][/tex]

So, the zeros of the quadratic function are:
[tex]\[ x = -1 - \sqrt{\frac{13}{6}} \quad \text{and} \quad x = -1 + \sqrt{\frac{13}{6}} \][/tex]

This matches the first option provided. Thus, the correct answer is:
[tex]\[ \boxed{x = -1 - \sqrt{\frac{13}{6}} \quad \text{and} \quad x = -1 + \sqrt{\frac{13}{6}}} \][/tex]